Centrally administered TNF increases arterial blood pressure independently of nitric oxide synthase. (August 2016) - Żera, Tymoteusz; Nowiński, Artur; Kwiatkowski, Piotr
Abstract: Introduction: Emerging evidence indicates that increased levels of TNF in the brain are associated with hypertension. Nitric oxide synthase (NOS) is involved in the central control of the cardiovascular system, exerting both pro- and antihypertensive effects. TNF induces hypothalamic synthesis of nitric oxide. Aim: We checked if acutely administered TNF into the cerebral ventricles affects arterial blood pressure, heart rate and baroreflex sensitivity, and whether TNF actions are dependent on NOS in normotensive rats. Methods: We carried out hemodynamic measurements in 6 groups of freely moving, adult Sprague-Dawley male rats, intracerebroventricularly (ICV) infused with either: 1) saline (5 μl/h); 2) TNF (200 ng/5 μl/h); 3) non-selective NO synthase inhibitor –l -NG-Nitroarginine Methyl Ester (l -NAME) (1 mg/5 μl/h); 4) TNF together withl -NAME (200 ng and 1 mg/5 μl/h, respectively); 5) neuronal NO synthase inhibitor – 7-nitroindazole sodium salt (7-NI) (20 μg/10 μl/h); 6) or TNF together with 7-NI (200 ng and 20 μg/10 μl/h, respectively). Mean arterial blood pressure (MABP), heart rate (HR) and spontaneous baroreflex sensitivity (sBRS) evaluated by the sequence method were analysed. Results: ICV infusion of TNF caused a significant increase in MABP accompanied by a transient increase in HR, and a decrease in sBRS. ICV infusion ofl -NAME increased MABP, but it did not change HR, nor sBRS. ICV infusion of 7-NI did not affect MABP, nor HR, nor sBRS. TNF administered together withl -NAME increased MABP with a transient increase in HR without changes of sBRS. Similarly, ICV infusion of TNF with 7-NI increased MABP without changes in HR and sBRS. Conclusions: Centrally administered TNF increases MABP and HR and blunts sBRS. The pressor effect of TNF appears to be independent of NOS activity in the brain. Inhibition of nNOS restores sBRS in TNF treated rats. Highlights: How does TNF administered into the brain affects blood pressure in conscious rats? TNF infused into cerebral ventricles increased arterial blood pressure. What is the contribution of nitric oxide synthase (NOS) to central TNF effects? Inhibition of brain NOS did not affect pressor action of TNF.